Investigation of Water Droplet Size Distribution in Conventional and Sustainable Aviation Turbine Fuels - Ugbeh, Judith; Carpenter, Mark; Okeke, Nonso (Cranfield University, 2022)
Water droplet size variation has been established in the literature as an important variable that influences the behaviour and characteristics of water in fuel emulsion. However, with the growing demand for sustainable aviation fuels (SAF), no data is available that shows how these fuels will affect dispersed water droplets’ size and frequency distribution. To address this lack of knowledge, this study explores and presents experimental results on the characterization of dispersed water droplets in alternative fuel and conventional Jet A-1 fuel under dynamic conditions. The alternative fuels comprised of two fully synthetic fuels, two fuels synthesised from bio-derived materials and one bio-derived fuel. The data and statistics presented reveal that water droplet frequency and size distribution are sensitive to changes in fuel composition. Observations show that the evident transition of the droplet’s percentile over time in the cumulative frequency distribution could be attributed to droplets coalescence to form larger droplets. Mean droplet diameters between 3 and 6 µm were observed for all the fuels tested. With further analysis based on recommendations proposed in this work, the data may assist in providing insight to filter manufacturers.
Keywords: 'Sustainable'; 'Turbine fuels'; 'Fuel systems'; 'Aviation'; 'Shedding'; 'Jet fuel'; 'Aircraft'; 'aerospace'; 'Aerospace Engineering'